Experiences of Shariah compliance department staff in providing spiritual care to hospitalised patients: a qualitative study - Wan Mamat, Wan Hasliza; Mohd Yusri, Intan Nabila; Azmi, Nor Azura; Arini, Merita; Muhammad Abdul Kadir, Fairuz Izzaty (IIUM Press, 2025)
Background: Spiritual care is a vital component of holistic healthcare, supporting patients in aligning with their beliefs to foster inner peace and overall well-being. However, there is limited research on the experiences of hospital staff in providing spiritual care. This study aims to explore the experiences of Shariah-compliant hospital staff in delivering spiritual care to hospitalised patients. Methods: A qualitative study was conducted through face-to-face interviews with eight purposively selected participants between April and May 2024 at a Shariah-compliant hospital in Malaysia. The interviews took place in the participants’ respective offices. With prior consent, all interviews were audio-recorded, transcribed verbatim, and analysed using thematic analysis. Results: Three major themes emerged from the analysis: (1) Addressing challenges in delivering spiritual care with the sub-themes: a) Resource constraints, b) Reluctant to talk, c) Frustration with patient, d) Emotional challenges, e) Role ambiguity, and f) Navigating family misunderstanding, (2) Strategies for effective spiritual care delivery with the sub-themes: a) Respectful communication, b) Listening and being present, c) Initiating spiritual conversations, d) Knowing the patient, e) Guiding through mentorship, and f) Be knowledgeable, and (3) Impacts of spiritual care to the patients with the sub-themes: a) Rediscovering faith, b) Behavioural change, c) Embracing acceptance, and d) Family support in well-being. Conclusion: Addressing challenges in spiritual care delivery and implementing effective strategies can enhance the provision of spiritual care, ultimately leading to improved patient outcomes. Future research should include diverse samples from various hospitals to deepen the understanding of spiritual care across different healthcare settings